Humanistic Literacy Diagnosis in the Implementation of Javanese Local Wisdom-Based Learning Models for Elementary School Students - Ari Metalin Ika Puspita; Hendrik Pandu Paksi; Vicky Dwi Wicaksono; Mulyani (MIMBAR PGSD Undiksha, 2023)
One of the problems of dehumanization that occurs in elementary school students is the decline in the values of noble character, fairness, honesty, empathy, respect, love of the country, humility, simplicity and forgiveness. The aim of the research is to diagnose the humanistic literacy of elementary school students by applying a learning model based on local Javanese wisdom. The research method used in this research is quasi experimental design. The research design chosen was pre-experimental with a one-shot case study model design. The research population is elementary school students. The number of test subjects for the instrument was 35 fifth grade elementary school students. The research sample was five elementary schools. The sampling technique in this research is purposive sampling. The number of research subjects was 165 fifth grade elementary school students. The data collection method is non-test. Data collection instrument with questionnaires. The data analysis technique for this research is the T Test (One Sample T-Test). The results show that the integrative learning model based on local Javanese wisdom has an influence on the humanist literacy of elementary school students. The implication of this research is that the learning model based on local Javanese wisdom has an influence on the increase in dehumanism that occurs in elementary school students after the Covid 19 pandemic. This condition can be seen from the increase in humanistic literacy indicators in students including collaboration, communication, critical thinking and creativity. It was concluded that the application of an integrative learning model based on local Javanese wisdom had a significant impact on the humanist literacy of elementary school students.